Crowdfunding agricultural ventures: psychological predictors of funding intentions and the role of climate change beliefs - Mark Ratilla; Diego Fernando Plata Lerma; Martina Rosíková; Khurram Ajaz Khan (Cogent Social Sciences)
Despite the popularity of crowdfunding models, backers’ support for agricultural ventures continues to lag, and knowledge of the psychological and environmental factors shaping consumers’ propensity to support such ventures remains limited. Hence, the study proposes a model based on social exchange theory and examines the effects of perceived risk, rewards, and prosocial factors on funding intentions. The role of climate change beliefs was also explored, given the vulnerability of agriculture to climate change impacts. The model was tested on 257 crowdfunding backers in the Philippines following the partial least squares structural equation modeling technique. The findings indicate that altruism and warm glow predict funding intentions. High levels of climate change belief increase financial and emotional reward expectations and decrease altruistic drives and herding effects. Practical insights are provided into designing strategies for backer targeting and initiatives to assist farmers in adopting climate change mitigation strategies and sustainable practices.